Western and Northern Lands as Polish reason of state in the thought and activities of Primate Stefan Wyszyński in the years 1948-1972 (with particular emphasis on archdiocese of Wrocław) - Kucharski, Wojciech (Studia Theologica Varsaviensia, 2019)
Primate Stefan Wyszyński engaged in a series of administrative and diplomatic activities related to the institution of the Polish Church organisation in the Western Lands. In the years 1948-1967 he exercised his authority over the Church in this area. He initially supervised apostolic administrators in Wrocław, Opole, Gorzów Wielkopolski, and in Olsztyn and Gdańsk, and after their removal in 1951 he sanctioned vicar capitulars elected by the state authority to preserved unity of the Church in Poland. In 1956 his attempts resulted in the restoration of the relevant bishops to their posts. In 1967 at his request the Pope Paul VI excluded the Church organisation in the Western Lands from the jurisdiction of Primate of Poland and subordinated it directly to the Holy See, instituting apostolic administrations there. primate repeatedly conducted negotiations with the Holy See in case of the institution of the Polish Church organisation in this area, which ended only after the ratification of the Polish-German treaty in 1972 by the announcement of the apostolic constitution Episcoporum Poloniae coetus. During the entire period Primate repeatedly visited archdiocese of Wrocław and supported the activities of the hierarchs governing this area, initially priest Karol Milik, and subsequently priest Kazimierz Lagosz and since 1956 bishop Bolesław Kominek. Primate Wyszyński repeatedly emphasised the rights of Poland to these lands in his speeches and sermons delivered in Wrocław. He proved that they resulted, on the one hand from their historical embeddedness in the Polish culture (he was referring to the relations of Silesia with Poland in the Piast period), and on the other hand he pointed to the re-Catholising mission of the Church in these lands. He also indicated that these lands are the peculiar compensation for the losses incurred by the Polish nation during the Second World War. He perceived the tasks of the Church in this area during the period of the stabilisation of the Polish Church administration as the Polish reason of state.